New species of Tingidae (Insecta: Heteroptera) from Madagascar - Guilbert, Eric (Zootaxa, 2020)
Surveys of Madagascar discovered five species new to science, described herein. A key to all species within the genera of these new species is provided, and the distribution of Malagasy Tingidae species is discussed.